Innovations and pitfalls in the use of wearable devices in the prevention and rehabilitation of running related injuries - Willy, R. W. (Physical Therapy in Sport, 2018)
Running-related injuries are common and are associated with a high rate of reoccurrence. Biomechanics and errors in applied training loads are often cited as causes of running-related injuries. Clinicians and runners are beginning to utilize wearable technologies to quantify biomechanics and training loads with the hope of reducing the incidence of running-related injuries. Wearable devices can objectively assess biomechanics and training loads in runners, yet guidelines for their use by clinicians and runners are not currently available. This article outlines several applications for the use of wearable devices in the prevention and rehabilitation of running-related injuries. Applications for monitoring of training loads, running biomechanics, running epidemiology, return to running programs and gait retraining are discussed. Best-practices for choosing and use of wearables are described to provide guidelines for clinicians and runners. Finally, future applications are outlined for this rapidly developing field. 1. Introduction 2. Why the need to quantify biomechanics and loading patterns in runners? 3. Overview of wearable devices 4. What makes a wearable device valuable? 5. Wearables and big data: predicting running performance and the epidemiology of running injuries 6. Use of wearables in returning the injured runner back to running 7. Future directions 8. Conclusion